Liability of PT. Pertamina Towards Fire Victims in Plumpang Reviewed Based on Civil Law Perspective - Jessica Audrey; Natasya Wijaya; Mochamad Habiibi (CV. Rayyan Dwi Bharata, 2023)
Indonesia is one of the countries with the largest population in the world. Economic factors are also the cause of the large number of Indonesian people, especially in the Capital City, who occupy illegal government-owned land to be used as residences, one of which is the land around PT. Pertamina. The people do not care about their own safety in order to have a place to live. This study aims to determine the form of responsibility for the occurrence of fires in Plumpang. This type of research is library research, namely research that takes data sources obtained through research of books related to the discussion of the issues to be discussed. The author also uses library data through books, books, articles, and journals that still have relevance to the topic of the problem to be discussed. Data collection method is done through descriptive method. The results obtained from this study are the demands of residents against PT. Pertamina is compensation for losses suffered by victims and knows the form of accountability provided by PT. Pertamina to the families of the victims.